The possibility of recasting of pure titanium - Pei-Ling Lai; Wen-Cheng Chen; Jen-Chyan Wang; Po-Sung Fu; Chih-Chiang Lin; Chun-Cheng Hung (Elsevier, 2017)
Background/purpose: Pure titanium (Ti) has many advantages, such as high corrosion resistance and excellent biocompatibility. The mechanical properties of pure Ti are like those of type IV gold alloys. Furthermore, gold alloys can be successfully recast in dental clinics. The aim of this study was to investigate the possibility of recasting pure Ti. Materials and methods: Magnesium oxide (MgO)-based investment that contained a 5 wt. % zirconium dioxide (ZrO2) additive was used. An argon-casting machine (Castmatic-S, Iwatani) was used to recast pure Ti. The first generation and second generation pure Ti (50 wt. % new Ti+50 wt. % surplus Ti) were used. Five specimens were fabricated and tested. The data were evaluated using two-sample t-test analysis (P<0.05). Results: The experimental results showed that recasting the Ti did not decrease the marginal accuracy, average surface roughness, Vickers hardness value of the superficial surface, and the thickness of the reaction layer. Conclusion: This study clearly showed Ti could be recast when a 5 wt. % ZrO2 additive MgO-based investment was used. This modified investment has the potential for use in clinical applications. Keywords: magnesia-modified investment, pure titanium, recasting